Pembuatan Logo Sebagai Strategi Pemasaran Olahan Kripik Ceker Ayam Desa Sampalan Tengah - Suputra, Komang Yudi; Gusi Putu Lestara Permana; I Gusti Ngurah Darma Paramartha; Adie Wahyudi Oktavia Gama; Putu Purnama Dewi; Sudiksa, I Made (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Marketing is a vital aspect of company that involves all activities aimed at promoting products or services, generating value for customers, and building lasting relationships. A logo is a distinctive emblem or visual representation created to promptly convey the unique identity of a firm and facilitate easy recall. The efficacy of a logo in attracting attention and establishing a powerful impact on consumers can be a determining element in distinguishing a product or service from rivals. One of the main challenges encountered by the producers of chicken foot chips in Sampalan Tengah village is the struggle to effectively promote their products, specifically in creating a distinct brand identity. The endeavor to design a logo and revamp the packaging, carried out in Sampalan Tengah village, is a tactical measure to reinforce product recognition, boost competitiveness, and offer the community's unique products to a wider market.